Nation size and unemployment - Norbert Berthold; Klaus Gründler (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, insbes. Wirtschaftsordnung und Sozialpolitik, 2011)
Throughout the world, strong dispersions of both regional and national unemployment rates can be observed. The economic theory has developed various explanations on how this differences occur. Corresponding models mainly aim at institutional and political framework, insider effects, efficiency wages, collective bargaining and cyclical effects. However, the size of economies has received little attention in this discussion. In this paper, we will show that there is indeed a strong link between size and unemployment. Using data from 37 countries, 15 continents and trade areas as well as 496 federal states, we will demonstrate that larger economic regions tend to have higher unemployment rates. Subsequently, we show that this correlation is strongly determined by the degree of centralization of countries. Based on these findings, we develop a model that explains regional and national unemployment using size and centralization. We will point out that centralization parabolas can be derived for each country. These curves are strongly influenced by the size of economies in a way that different sizes lead to a shift of the parabolas. As we will demonstrate, country-specific parabolas explain the strong dispersion of unemployment rates quite accurately.
Keywords: J64; J08; R10; F00; 330; unemployment; size; centralization